Students’ Perception on The Use of WhatsApp for Learning Writing During Covid-19 Pandemic: A Case Study - Elvira Rosalinda; Hamamah Hamamah; Putu Dian Danayati Degeng (Lembaga Penelitian dan Pengabdian Universitas Nahdlatul Ulama Blitar, 2022)
Writing skill is a complex skill that cannot be learned independently. Although students learn from home, they need a comprehensive understanding of theories and practical guidance from the teacher. Therefore, teachers use many media and applications that can support this online learning with various considerations. This research is conducted to find out the nine-grade students’ SMPN 04 Pare perception of the use of WhatsApp groups for learning writing. This research used a case study to identify students’ perceptions in the IX C class of SMPN 4 Pare. There were 31 students responded to the questionnaire. In analyzing the data, descriptive statistics were used. The writer used mean as the measurement to determine the percentage of students’ perception. The result shows that students have posiive responses to the use of WhatsApp in learning writing. The students show strong interest in the usage of WhatsApp for learning writing platform and the learning activities that were done through WhatsApp.